2014
DOI: 10.3892/ijmm.2014.1943
|View full text |Cite
|
Sign up to set email alerts
|

Xuebijing exerts protective effects on lung permeability leakage and lung injury by upregulating Toll-interacting protein expression in rats with sepsis

Abstract: Xuebijing (XBJ) is a type of traditional Tibetan medicine, and previous pharmacological studies have shown that the ethanol extract is derived from Chuanxiong, Chishao, Danshen and Honghua. Chuanxiong, Chishao, Danshen and Honghua possesses potent anti-inflammatory activity, and has been used in the treatment of inflammatory infectious diseases. In the present study, we investigated the effects of XBJ on pulmonary permeability and lung injury in cecal ligation and puncture (CLP)-induced sepsis in rats. A CLP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…Endotoxin causes different types of tissue and organ damages, and XBJ injection exhibited antagonistic effects against endotoxin toxicity in different animal models [1819]. Of particular interest to our current study, XBJ inhibited the expression of TREM-1 by antagonizing endotoxin [38], through which it decreased the level of Toll-like receptor 4, hence reducing the production of inflammatory cytokines to protect organ functions [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin causes different types of tissue and organ damages, and XBJ injection exhibited antagonistic effects against endotoxin toxicity in different animal models [1819]. Of particular interest to our current study, XBJ inhibited the expression of TREM-1 by antagonizing endotoxin [38], through which it decreased the level of Toll-like receptor 4, hence reducing the production of inflammatory cytokines to protect organ functions [39]. …”
Section: Discussionmentioning
confidence: 99%
“…As a feature of sepsis, capillary leakage represents an endothelial barrier dysfunction, which can be induced by the secretion of inflammatory cytokines that increase endothelial permeability (26). The dangers of capillary leakage include increased tissue edema, cell hypoxia and the excessive local accumulation of inflammatory cytokines, which directly lead to tissue and cell damage and can induce MODS or MOF (27).…”
Section: Discussionmentioning
confidence: 99%
“…[89] Xuebijing, a traditional Chinese medicine preparation, has functions of anti-infl ammation, neutralizing endotoxin and regulating immune cells, etc. Animal experiments [90,91] showed that Xuebijing reduced the mortality of septic mice. A single center clinical study found that Xuebijing could promote the stabilization of hemodynamics and improve the outcome of patients with sepsis complicated with DIC.…”
Section: Subcutaneous Injection Of Thymosin and Intravenousmentioning
confidence: 99%